Detection and Identification of Salmonella enterica, Escherichia coli, and Shigella spp. via PCR-Electrospray Ionization Mass Spectrometry: Isolate Testing and Analysis of Food Samples - Pierce, Sarah E. (American Society for Microbiology, 2012)
An assay to identify the common food-borne pathogens Salmonella, Escherichia coli, Shigella, and Listeria monocytogenes was developed in collaboration with Ibis Biosciences (a division of Abbott Molecular) for the Plex-ID biosensor system, a platform that uses electrospray ionization mass spectroscopy (ESI-MS) to detect the base composition of short PCR amplicons. The new food-borne pathogen (FBP) plate has been experimentally designed using four gene segments for a total of eight amplicon targets. Initial work built a DNA base count database that contains more than 140 Salmonella enterica, 139 E. coli, 11 Shigella, and 36 Listeria patterns and 18 other Enterobacteriaceae organisms. This assay was tested to determine the scope of the assay's ability to detect and differentiate the enteric pathogens and to improve the reference database associated with the assay. More than 800 bacterial isolates of S. enterica, E. coli, and Shigella species were analyzed. Overall, 100% of S. enterica, 99% of E. coli, and 73% of Shigella spp. were detected using this assay. The assay was also able to identify 30% of the S. enterica serovars to the serovar level. To further characterize the assay, spiked food matrices and food samples collected during regulatory field work were also studied. While analysis of preenrichment media was inconsistent, identification of S. enterica from selective enrichment media resulted in serovar-level identifications for 8 of 10 regulatory samples. The results of this study suggest that this high-throughput method may be useful in clinical and regulatory laboratories testing for these pathogens.